Polarization-Insensitive Silicon Nitride Photonic Receiver Based on Thin Waveguides for Optical Interconnects at 1 $μ$ m - Alexander Caut; Magnus Karlsson (IEEE Photonics Journal, 2024)
This article demonstrates with simulations two polarization independent wavelength division multiplexing receiver platforms based on thin silicon nitride waveguides for optical interconnects at 1 $μ$ m. The chosen waveguide base geometry (width = 900 nm × height = 160 nm) is a good tradeoff between mode confinement and propagation loss. We first propose a design using a polarization splitter with an 1×4 demultiplexer based on an arrayed waveguide grating (AWG). This receiver has a reduced size and requires only one etching step. We later propose another simplified receiver design using a polarization splitter-rotator with two identical 1×4 demultiplexers based on cascaded Mach-Zehnder interferometers. The rotator is based on a thicker waveguide (width = 500 nm × height = 400 nm) and is partially etched to rotate the electric field by 90 $^{° }$ . Thus, it requires the use of mode size converters at the in/output ports. To keep the fabrication complexity as low as possible for the second design, we limited ourselves to only two etching steps. Therefore, the thickness of the slab of the mode converters and of the rotator is the same as for the main 900 nm (wide) × 160 nm (thick) waveguide. The simulated extinction ratio of the polarization splitter at 1035 nm is 18 dB and the calculated TM-TE and TE-TM polarization conversion efficiency of the polarization rotator at 1035 nm is 99.9 $%$ .